2022
DOI: 10.3390/su14148422
|View full text |Cite
|
Sign up to set email alerts
|

Durable Icephobic Slippery Liquid-Infused Porous Surfaces (SLIPS) Using Flame- and Cold-Spraying

Abstract: Icing and ice accretion cause severe problems in different industrial sectors, e.g., in aircrafts, aviation traffic, ships, solar panels, and wind turbines. This can lead to enormous economic losses and serious safety issues. Surface engineering can tackle these problems by designing surface structures to work as icephobic coatings and, this way, act as passive anti-icing solutions. In this research, slippery liquid-infused porous structures were fabricated using flame- and cold-spraying to produce polymer (LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 111 publications
0
6
0
Order By: Relevance
“…The image (image-charge) forces were shown to considerably contribute to the stability of wetting films of nonpolar liquids on various substrates. ,,,, However, due to the mathematical complexity of the problem, so far, only the single-layer wetting films were considered analytically. Meanwhile, as noted above, the most prospective state-of-the-art applications of liquid-infused surfaces usually involve stratified films that contain at least two thin dielectric layers. To correctly account for the effect of image forces on the stability of a lubricating film, we first consider the electrostatic problem of the distribution of electric potential and electric field strength in two model systems imitating the conditions of the lubricating layer in slippery coatings as sketched in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The image (image-charge) forces were shown to considerably contribute to the stability of wetting films of nonpolar liquids on various substrates. ,,,, However, due to the mathematical complexity of the problem, so far, only the single-layer wetting films were considered analytically. Meanwhile, as noted above, the most prospective state-of-the-art applications of liquid-infused surfaces usually involve stratified films that contain at least two thin dielectric layers. To correctly account for the effect of image forces on the stability of a lubricating film, we first consider the electrostatic problem of the distribution of electric potential and electric field strength in two model systems imitating the conditions of the lubricating layer in slippery coatings as sketched in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Thermal spray coating is a cost-effective and eco-friendly option for the fabrication of SLIPS substrates using specific spray parameters. Low-pressure cold spray and flame spray are preferred methods: while the cold spray is ideal for the on-site fabrication of thick, multi-layer polymer coatings on heat-sensitive substrates, the flame spray method is more suitable for creating high-porosity polymer coatings [108]. The most commonly used polymers are low-density polyethylene and polyether ether ketone.…”
Section: Surface Structurementioning
confidence: 99%
“…The most commonly used polymers are low-density polyethylene and polyether ether ketone. Flame-sprayed polyethylene coatings (FS-PE) show greater oil locking than cold-sprayed polyethylene (CS-PE) and polyether ether ketone (CS-PEEK) coatings due to their evenly distributed and closed-cell structures, which retain more lubricant under shear stress [108]. Yuanzhe et al used a titania-polyurea (TiO 2 -SPUA) spray coating to construct a regularly hydrophobic surface texture on a polyurea coating system [109].…”
Section: Surface Structurementioning
confidence: 99%
See 1 more Smart Citation
“…This process resulted in the formation of a continuous and smooth liquid lubricant film, enabling water droplets to effortlessly slide off, even at a small contact angle [5][6][7]. Due to the excellent water repellency and low ice adhesion strength, the SLIPS demonstrated great potential in anti-icing applications [8][9][10][11]. For instance, Wilson et al [12] found that the SLIPS could significantly reduce the nucleation temperature of supercooled water in contact, with statistical significance, and showed no deterioration or change in the coating performance even after 150 freeze-thaw cycles.…”
Section: Introductionmentioning
confidence: 99%